Gender disparity and pattern of literacy: An analysis of scheduled tribes of Jharkhand, India - Alka Rani; Sanjay Kumar (National Geographical Journal of India, 2023)
Gender gap in literacy is the result of gender-based discrimination that creates barriers for girls, and women to enjoy their equal human right. Gender prejudice results gender discrimination from childhood. In Jharkhand, the literacy of tribal population is only 57.1% which is less than the national tribal average. There exists a gap of 21% in male-female literacy of tribal population of Jharkhand, which is the matter of urgent concern to talk about female education to reduce disparity in literacy which ultimately promotes overall development of women in the society especially for the tribal communities. Hence, this paper attempts to find out the district wise regional variation in disparity in literacy and pattern of literacy among the tribal population of Jharkhand. The present study reveals that majority of the districts have low female literacy and shows the high gender gap in literacy and reasons like poverty, low educational level of parents, week family structure and domestics problem which negatively effects the value of education. The study uses, secondary data from Census of India, 2011 and modified Sopher’s Disparity